DIGITAL ENGLISH: HOW TECHNOLOGY CHANGES THE WAY WE LEARN - Kamola Kayumova; Abdujalilova Shahrizoda (Bright Mind Publishing, 2025)
In the digital age, learning is no longer confined to chalkboards and textbooks. This essay explores how technology has changed the way we learn, especially in higher education, by examining access to resources, teaching–learning processes, and student experience. Drawing on global research and reflecting on real university life, the paper argues that technology offers real advantages but must be used thoughtfully. The overall tone is student-centred and reflective: as a learner myself, I invite you to consider these changes alongside me.
Keywords: Digital learning, educational technology, higher education, personalised learning, student engagement, pandemic teaching, adaptive learning